2012
DOI: 10.1371/journal.pone.0045339
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin Expression Contributes to Human Transurothelial Permeability In Vitro and Is Modulated by NaCl

Abstract: It is generally considered that the bladder is impervious and stores urine in unmodified form on account of the barrier imposed by the highly-specialised uro-epithelial lining. However, recent evidence, including demonstration of aquaporin (AQP) expression by human urothelium, suggests that urothelium may be able to modify urine content. Here we have we applied functional assays to an in vitro-differentiated normal human urothelial cell culture system and examined both whether AQP expression was responsive to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 31 publications
4
34
0
Order By: Relevance
“…non-diseased, human urothelium expresses several AQPs, suggesting a potential role in water and urea transport across the urothelial layer 2 . Predominant expression of AQP3 is supportive of the hypothesis that the urothelium may be able to modify volume and final composition of the urine 3 . Apart from its crucial significance in human physiology, there is strong presumptive evidence that AQPs play a role in carcinogenesis, such as in tumour angiogenesis and cell migration 4 . On the basis of our findings in normal human urothelium, we have previously investigated the expression and potential significance of AQPs in UBC and showed that there is a significant correlation between AQP3 protein expression and tumour stage and grade, with AQP3 expression being reduced or lost in tumours of higher grade and stage.…”
Section: Introductionsupporting
confidence: 65%
“…non-diseased, human urothelium expresses several AQPs, suggesting a potential role in water and urea transport across the urothelial layer 2 . Predominant expression of AQP3 is supportive of the hypothesis that the urothelium may be able to modify volume and final composition of the urine 3 . Apart from its crucial significance in human physiology, there is strong presumptive evidence that AQPs play a role in carcinogenesis, such as in tumour angiogenesis and cell migration 4 . On the basis of our findings in normal human urothelium, we have previously investigated the expression and potential significance of AQPs in UBC and showed that there is a significant correlation between AQP3 protein expression and tumour stage and grade, with AQP3 expression being reduced or lost in tumours of higher grade and stage.…”
Section: Introductionsupporting
confidence: 65%
“…AQP0, 1, 2, 5, 6, 8, 10 and 12, however, were not expressed. In a subsequent paper, those same authors suggested that the urothelium of the ureters and bladder might be responsible for serving a modulatory role in water and salt homeostasis, although they did not confirm it to be so in vivo in humans …”
Section: Discussionmentioning
confidence: 97%
“…After physical or other damage, the urothelium will self-repair by switching from a mitotically quiescent to a highly regenerative state (20,28). The urothelium has inbuilt mechanisms for responding to changes in urinary salt concentration (18) and for initiating the innate immune system after exposure to uropathogenic Esherichia coli (21). Thus, the urothelium may be considered a hub for sensing and transducing information to other tissue compartments and acting to coordinate physiological bladder function and responses.…”
mentioning
confidence: 99%